PAI STUDENTS' PERCEPTION OF THE CLASS OF 2022 TOWARDS THE USE OF LEARNING MODELS BY PAI STUDY PROGRAM LECTURERS AT UIN AR-RANIRY - Al-Fata Chalid; Ramli (Al-Mubin, 2026)
This study aims to determine the perceptions of Islamic Religious Education (PAI) students from the 2022 cohort regarding the use of learning models by lecturers in the Islamic Religious Education Study Program at UIN Ar-Raniry Banda Aceh. The research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving 15 students as research subjects. The results indicate that most lecturers still predominantly use traditional methods such as lectures, discussions, and question-and-answer sessions, while the implementation of innovative learning models remains limited. This condition causes some students to feel bored and less motivated. However, several lecturers have implemented active learning models, such as problem-based learning and group discussions, which are considered effective in increasing students’ enthusiasm and understanding. Overall, students expect the implementation of more varied, interactive, and technology-relevant learning models so that the learning process becomes more effective and meaningful.